Single molecule thin film featuring disubstituted thiourea (TU) doped with chlorophyll as potential active layer in photovoltaic cell - Wan M, Khairul,; Mohd Fairuz, Yusof,; Rafizah, Rahamathullah; Adibah Izzati, Daud; Siti Maryam, Jasman,; Mohd Faizuddin, Abu Hasan; Hasiah, Salleh; Hasyiya Karimah, Adli; Meng Guan, Tay (Electrochemical Science Publisher, 2013)
The versatility of conjugated thiourea compound enhances the development of molecular wire architectures due to the overlapping of Ï€-electrons which can be applied as potential organic solar cell (OSC). Hence, new innovational and breakthrough are needed for OSC molecules to become competitive in the future since they represent lower cost and more flexible devices, tunable electronic properties and easier processing compared to other organic molecules. Due to this interest, a study on the performance of essentially linear conjugated organic compound based on Donor (D)-Ï€-Acceptor (A) system which featuring D-ArNHC=SNH-A-NHC=SNHAr-D to act as potential active layer in OSC was carried out. The synthesized compound was successfully designed, prepared, and characterized prior to form thin film. The compound was then spectroscopically and analytically characterized via Â¹H and 13C Multi-Nuclear Magnetic Resonance (NMR), Fourier Transform Infrared (FT-IR), UV-Visible Analysis (UV-Vis), Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM), CHNS Elemental Microanalysis as well as Cyclic Voltammetry (CV) analysis. In turn, it was fabricated on Indium Tin Oxide (ITO) substrate before its conductivity behaviour, efficiency and OSC parameter were evaluated by Four Point Probe. From the electrical conductivity study, it revealed that it performed better and higher conductivity with the presence of chlorophyll (CHLO) under maximum light intensity of 100 Wm-2. The result shows the electrical conductivity increases with the increasing of the light intensity. The electrical conductivity of the thin films shows the conductivity of 0.2040 Scm-1 (with CHLO) compares to 0.1472 Scm-1 (without CHLO) under maximum light intensity. From the result obtained, it clearly shows the synthesized compound has great potential to act as an active layer in photovoltaic cell. Therefore, further investigation on photovoltaic studies on the similar molecular system should be seriously considered for further development in molecular electronics application.